The analysis of efficiency of risk-based approach in supervision activities of Federal Tax Service in the system of state financial monitoring - E. I. Brichka; I. A. Kolesnik; Yu. S. Zharkova (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the issues of risk-oriented supervision in the activities of the Federal Tax Service, which is an integral part of the state financial monitoring of Russia. Modern practice shows that the increased pressure of tax services on taxpayers causes the growth of the «shadow sector» in the economy, at the expense of small and medium-sized enterprises experiencing uncertainty before the supervisory authorities. The strategy of increasing the number of office and field audits has little effect in motivating tax payments. Taxes are an integral institutional element of a market economy, which is both an economic and a legal category. The economic content of taxes consists in the redistribution of the gross national product and reflects the relationship to mobilize part of the income that is formed in the private sector at the disposal of the state. As a result, tax evasion, which is one of the predicate crimes, by organizations causes the growth of the shadow economy and contributes to the processes of money laundering. In this regard, the tasks of justifying the need to modernize the risk management system when implementing tax control in Russia and analyzing the introduction of a modern risk-based approach to tax supervision in order to stabilize the country’s financial system are very relevant. The purpose of the article is to formulate conclusions on the effectiveness of the application of the risk-based approach in the supervisory activities of the Federal Tax Service.